R&D Tahap Assesment: Keefektifan Bahan Ajar Statistik Pendidikan Berbasis LC 5E Berbantu Minitab - Abdillah, Agus; Prasetyono, Hendro; Rizkiyah, Nur; Fitria, Dona; Burhanudin, Burhanudin (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
One indicator that learning can be said to be effective is optimal learning outcomes. In fact, to achieve the word "effective" is still far from expectations. These problems cannot be separated from how the lecturers should apply appropriate learning models. This research is the R&D stage of testing the effectiveness of teaching materials using a non-equivalent control group design. The population of all students of the Economic Education Study Program, Indraprasta PGRI University Semester V of the 2020/2021 academic year consists of 31 classes with 1175 students. The sample taken is class S5F (experiment class) as many as 42 people and Class S5E (control class) as many as 43 people. The analysis technique used is the independent t-test. The results of the descriptive analysis showed that the experiment class obtained an average value of learning outcomes that was higher than the control class (80.61 > 74.02). While inductive analysis obtained t_statistic > t_table (4.209 > 1.989). This means that there is a significant difference in learning outcomes between the experiment class and the control class. Therefore, it can be concluded that the Educational Statistics teaching material based LC 5E assisted by Minitab is very effective in its use in learning